Closing Europe’s Cardiovascular Implementation Gap: A Critical Review of the Safe Hearts Plan and the Cyprus Test Case - Georgios P. Georghiou; Sotiris Kyriakou; Panos Georghiou; Amalia Georgiou; Nikolas Iosif; Konstantinos Toutouzas; Andrew Xanthopoulos; Konstantinos Lampropoulos; Argyris Kyriakou; Filippos Triposkiadis (Journal of Clinical Medicine, 2026)
Cardiovascular disease remains Europe’s leading cause of death and disability despite mature evidence for prevention, acute and chronic treatment, rehabilitation, and secondary prevention. This structured critical narrative review evaluates whether the European Safe Hearts Plan can convert this evidence into coordinated, measurable, and accountable cardiovascular pathways. We appraise the plan’s ten flagship actions by evidence maturity and implementation readiness; distinguish shared system functions from disease-specific delivery for acute coronary syndromes, heart failure, and atrial fibrillation; compare selected European Society of Cardiology and American Heart Association/American College of Cardiology recommendations; and propose a core indicator set and staged Cyprus pilot. Guideline-supported interventions should be standardised and audited, whereas screening technologies, digital health, artificial intelligence, and novel phenotyping require governed implementation and prospective assessment of patient outcomes, costs, equity, and unintended consequences. Cyprus is presented as a bounded implementation setting rather than a directly generalisable European model. The plan should be judged through a limited set of clinical, implementation, and equity indicators, including premature cardiovascular mortality, risk factor control, guideline-directed therapy, rehabilitation participation, registry completeness, reach, and fidelity.